(untitled) (Altre Modernità, 2018)
Forms of knowledge and our understanding of the world are central concerns in Amitav Ghosh’s fiction. His novels often deconstruct epistemology derived from the Western philosophical tradition, with the aim of pointing at its relativity in spite of its claim to universality. This essay wants to demonstrate how The Calcutta Chromosome (1996) closely connects the production of an alternative form of knowledge (the counter-science) with a different way of perceiving and conceiving space. Focusing specifically on Calcutta’s urban space, it will examine the correlation between space and epistemology in the novel through three spatial and gnoseological categories: borders, the labyrinth, and, finally, networks.